IN-VITRO ANTIOXIDANT AND IN-VIVO HEPATO PROTECTIVE ACTIVITY OF ETHANOL EXTRACTS FROM THE BARK OF SHOREA ROBUSTA (DIPTEROCARPACEAE) AGAINST CARBON TETRA CHLORIDE INDUCED LIVER TOXICITY IN RATS - Biswas, Diptanu (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT: The study is designed for the evaluation of in-vivo Hepato protective and in-vitro Anti oxidant activity of ethanol extracts from the bark of Shorea robusta (Dipterocarpaceae) by CCl4 induced hepatotoxicity in rats. Ethanol extracts from the bark Shorea robusta (EESR) was evaluated for hepatoprotective activity in rats by inducing liver damage by CCl4. The anti oxidant activity of EESR was assayed by various in-vitro antioxidant methods and activities were compared to standard ascorbic acid. Ethanol extracts at an oral dose 200mg/kg and 400mg/kg exhibited a significant (*p<0.005) protective effects by lowering the level of SGOT, SGPT, ALP, Serum bilirubin, total cholesterol and increasing the level of total proteins as compared to Silymarin (50mg/kg) used as positive control. The extracts exhibit significant anti oxidant activity in various in vitro anti oxidant models. Â From these studies we are concluding that, the ethanolic extracts of S.robusta have potent hepatoprotective effects and have anti oxidant properties, hence can be used as a natural product against liver damage. KEY WORDS: Anti oxidant, Carbon tetra chloride, Â Hepatoprotective, Â Shorea robusta